ROH KUDUS PEMBERI KEKUATAN DAN PENEGUHAN Analisa Wacana Kritis Terhadap Narasi Efesus 3:16-17 - Petrus Baela; Mahattama Banteng Sukarno (SAGACITY : Journal of Theology and Christian Education, 2021)
The Holy Spirit is part of the discourse that develops in the communities of Christ’s disciples. The Holy Spirit becomes a discourse, because it is closely related to social praxis in social interactions and experiences, both in the community of believers and the general public. This study tries to understand how the function of the discourse about the “Holy Spirit, The Giver of Strength and Affirmation’ in the text of Ephesians 3:16-17. Functionally, there are at least two things, among others: first, the Holy Spirit as the Giver of Strength and Confirmation of Faith; and second, the Holy Spirit as the Giver of Strength and Affirmation in maintaining a substantial identity. Both functions can be performed, when the Holy Spirit is in the inner man. These conditions will help humans to have a complete self-awareness of the mystery of Christ. The mystery of Christ which is understood only using reason will lead to division, but if assisted by the Holy Spirit who is in the heart, the mystery of Christ will lead to salvation and peace.